Microstructures and mechanical properties of novel 2.3 GPa secondary hardening steels with different Ni contents - Wenhong Peng; Yichen Wu; Ruming Geng; Yuxian Cao; Shun Han; Yong Li; Chunxu Wang; Lijing Zheng (Journal of Materials Research and Technology)
The development of ultra-high strength steels with balanced ductility and toughness is of significant industrial importance. In the present study, impact toughness, tensile properties, and microstructural evolution of high-Co-Ni secondary hardening steels were investigated by adding Ni from 13 to 15 wt%. Within a certain range, Ni effectively refines the grain size and the thickness of austenite films, facilitating the enrichment of Ni in nanoscale film reverted austenite, thereby enhancing the austenite stability and toughness in steels.At a Ni concentration of 14 wt%, the steel exhibits the most refined martensitic substructure and nanoscale film-like reverted austenite, enriched with Ni, along with the precipitation of a significant volume of nanoscale semi-coherent (Mo,Cr)2C phases. This microstructural configuration yields an optimal synergy of strength and toughness, with an ultimate tensile strength reaching approximately 2.3 GPa and a Charpy impact energy of around 34 J. However, an increment in Ni content results in a higher volume fraction of Ni-enriched reverted austenite, which poses challenges to eliminate during low-temperature and aging processes, consequently reducing the steel's toughness. This comprehensive study provides a foundation for the design of ultra-high-strength alloys with tailored strength and toughness, highlighting the pivotal role of Ni in achieving this balance.